An intraslab seismic sequence activated by the 2011 Tohoku‐oki earthquake: Evidence for fluid‐related embrittlement. Issue 7 (16th July 2013) - Nakajima, Junichi; Yoshida, Keisuke; Hasegawa, Akira
Abstract [1] Using quantitative analysis of waveforms, we investigate a seismic cluster that occurred at a depth of 67 km in the Philippine Sea slab 8 months after the 11 March 2011 megathrust Tohoku‐oki earthquake (Mw 9.0). The sequence started with an M 4.1 normal‐fault event on 14 November in the deepest part of the cluster, and subsequent earthquakes migrated upward by 6 km along a narrow conduit‐like zone. The earthquakes have stress drops of 0.5–40 MPa, and groups of earthquakes with coherent waveforms are observed. We explain these observations in terms of fluid‐related embrittlement and the migration of overpressured fluids. The low‐permeability plate interface of the Pacific plate may have been broken by the coseismic or postseismic slips of the Tohoku‐oki earthquake, with the fluids subsequently being liberated from the underlying crust of the Pacific slab and migrating into the Philippine Sea slab due to the pore pressure gradient. The tensional stresses generated by the coseismic slip promoted the efficient upward migration of fluids and also acted to enhance the deviatoric stress around the source area. The heightened pore pressures and the resulting reduced effective normal stress lowered the strength of the faults sufficiently to bring the system into the brittle regime under the enhanced deviatoric stress. The lag of 8 months may represent the time needed for the unsealing of the plate interface, the upward migration of fluids, and the increase in pore pressure to become sufficient to overcome the lithostatic pressure.